The Expression of microRNA-155 and mRNA Hypoxia Inducible Factor Alpha (HIF1A) in the early and advanced stages of ovarian cancer patients blood plasma - S.N. Chasanah; A.S. Fitriawan; F.K. Pukan; A.I. Kartika; R, Oktriani; A. Trirahmanto; H. Pradjatmo; T. Aryandono; S.M. Haryana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Ovarian cancer has the problem turned out to be the greatest and almost half the death rate of mortality throughout gynecological malignancy. Ovarian cancer is found in the female reproductive organs and the second most common cancer after cervical cancer. The process of carcinogenesis of ovarian cancer occurs at the molecular level, regulated by microRNA. At in silico research that has been done, it is known that microRNA-155 (miR-155) targeted mRNA HIF1A which is the regulator genes in hypoxia conditions. HIF1A involved in various cancer hallmarks, where some of them have roles in Warburg effect and also as genetical transcription factors in angiogenesis. Regulation of miR-155 and mRNA HIF1A believed to be involved in the process of ovarian cancer progression and thus potentially as minimally invasive biomarker for prognosis. The aim of this study is to determine whether there are differences in the expression of miR-155 and mRNA HIF1A in plasma ovarian cancer patients at the early stage compared with the advanced stage.The samples using blood plasma from ovarian cancer patients RSUP Dr. Sardjito with 32 ovarian cancer patients early stages and 20 ovarian cancer patients advanced stages. Total RNA was isolated from blood plasma samples of ovarian cancer patients.  cDNA synthesis from total RNA was performed to obtain cDNA. The expression of miR-155 and HIF1A were calculated using qPCR. qPCR results were analyzed using Biorad CFX Manager Software. The analysis showed that the expression of miR-155 were 2,18 times lower (p-value = 0,018*) in the plasma of advanced stage ovarian cancer compared with early stage, the differences were statistically significant (p value≤ 0,05). Whereas the mRNA expression HIF1A were 2,46 times higher (p-value = 0,039*) in the plasma of advanced stage ovarian cancer compared with early stage, the differences were statistically significant (p value≤ 0,05). This study has proved that miR-155 expression is downregulated and followed by upregulation of mRNA expression HIF1A at an advanced stage ovarian cancer compared with early stage.  Keywords: Plasma, stage ovarian cancer, microRNA-155, mRNA HIF1A